Pengaruh Daun Salam (Syzygium polyanthum) Terhadap Kadar Trigliserida Dan Kolesterol Total Darah Pada Penderita Dislipidemia - Lovina Ramadhita Agung (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Background: Dyslipidemia results from abnormalities in lipid metabolism or plasma lipid transport or disturbances in the synthesis and degradation of plasma lipoproteins characterized by an increase or decrease in the lipid fraction in plasma. Bay leaf (Sygium polyanthum) is a plant whose leaves are widely used for flavoring in Indonesian cuisine, in its use, bay leaves have many benefits and other properties, one of which can be used as herbal medicines for cholesterol disease. Objective: to determine the effect of bay leaf extract (Syzygium polyanthum) on triglyceride and total blood cholesterol levels. Methods: Using literature studies from both national and international journals by summarizing the discussion topics and comparing the results presented in each article. Result: Behind its health benefits, bay leaves are very easy to find in Indonesia. The decrease in cholesterol levels by giving bay leaf extract can occur because bay leaves (S. polyanthum) contain flavonoids, one of which is quercetin. Quercetin can inhibit the oxidation of LDL that has been modified by macrophages, namely by reducing the content of to-tocopherol contained in LDL particles. Flavonoids also work by inhibiting the HMG-CoA Reductase enzyme so that cholesterol synthesis decreases resulting in decreased blood cholesterol levels. Conclusion: giving bay leaves can reduce excessive triglyceride and total blood cholesterol levels.